Produção e qualidade de frutos de tomateiro cereja cultivados em diferentesespaçamentos em sistema orgânico - Denilson de Oliveira Guilherme (2007)
Cherry tomato despite of being a vegetable with a great consumer value needs to be more studied to improve its handling. For these reason, the objective of this work was to evaluate the development of genotypes of cherry tomato in different spacings in organic management, in the soil and climate conditions of the North of Minas Gerais state. The treatments, in a factorial scheme 3 x 4, With the 3 genotypes of cherry tomato (two ancestries: CH152 and CLN1561A and the variety Carolina ") and 4spacings between plants (0,40; 0,60; 0,80; 1,00m). The experimental design was random blocks with 3 repetitions. The productivity characteristics of the plant and quality of the fruits had been determined. The highest commercial productivity had been presented by genotypes CLN 1561A and the "Carolina type. In conclusion we found that the highest productivity was observed in the lesser spacing, having beenthe production of fruits for area influenced by the spacing. The tested genotypes had presented good performance of field for the soil and climate conditions of the semiarid region of Minas Gerais state under organic management.